Social Work in 40 Objects: Teaching and learning in the language of things - Doel, Mark (Cuadernos de Trabajo Social, 2021)
This article considers the significance of a web-based experimental project that aims to discover how social work might be displayed and demonstrated via a collection of Objects. An open access approach invited participants to ‘donate’ an object and to tell the story of how and why the object connects them to social work. The aim is to find a way to express the contested nature of social work in a more immediate and accessible way than text book definitions can achieve.The experiment is quantitatively successful (more than 150 objects from 25 different countries); in qualitative terms, the objects donated to the website have elicited a very broad range of themes in entertaining and engaging ways. The exhibition has ‘toured’ to many countries where it proves to be adaptive to cultural differences and gives rise to spontaneous object donation, thus proving its relevance and immediacy. Understanding social work via Objects has been used successfully to teach students about the contested nature of social work theory and practice.
Keywords: charged objects; experimental website; material culture theory; professional identity; social work practice